Analysis of sustainability accounting standards: a review - Yeşil, Tolga (Entrepreneurship and Sustainability Issues, 2024)
The United Nations (UN), one of the international organizations, carries out various studies within the framework of their objectives for protecting the environment for sustainable development and against the climate crisis. This study is also an academic written source that supports the UN's goals. This study conducted a bibliometric analysis of 128 articles scanned in the Web of Science SSCI index within the scope of sustainability accounting standards. Because of the study, it is noteworthy that there has been an increase in the number of publications on sustainability accounting standards after 2017. In recent years, enterprises have increased awareness about sustainability, and accordingly, they attach importance to environmental practices in the production process. Another finding is that the publications are mostly co-authored, and these authors are from different countries. In this regard, it was observed that the authors who contributed the most works were from Spain. As a result of creating a word cloud image, it was determined that the word sustainability was the most frequently used keyword. The analysis revealed that the journal "Sustainability" publishes the most works on this subject. This study, a reference source for new studies, is thought to contribute to the international literature.